Production Performance of Improved Poultry under Backyard Farming System in Hill Agro-Climatic Condition in West Bengal - Roy, Rakesh; Monda, Tista; Moktan, M. W. (Indian Journal of Hill Farming, 2018)
Backyard poultry is primarily kept for egg and meat production on a subsistence basis in rural areas of India. Farmers usually rear desi/native type chicken having low egg and meat production potential. Krishi Vigyan Kendra (KVK), Kalimpong; the farm science centre of Uttar Banga Krishi Viswavidyalaya, demonstrated improved breeds of backyard poultry in selected farmers’ field to scale up the practice in the locality by proving their potential over the local strains at micro farming situation. The present study has been conducted on two improved purebred poultry with primary objective to study the laying performance, egg production, morbidity and mortality rate and preference of farmers towards the improved poultry breed in hill agro-climatic condition. A total of 1442 Vanaraja birds, 1576 RIR birds and 986 desi birds were considered under study from 180 farmers selected for data collection. Preferences for improved poultry breeds among farmers were assessed in Garrett Ranking Method. The result shows that Vanaraja male and female attained an average weight of 0.67kg & 0.53kg, 1.54kg & 1.09kg, 2.76kg & 2.14 kg, 4.09kg & 3.48kg and 5.15kg & 4.42kg at the age of 4weeks, 10weeks, 20weeks 40weeks and 72weeks respectively. RIR male and female attained an average weight of 0.61kg & 0.52kg, 1.41kg & 1.04kg, 2.55kg & 2.11 kg, 3.04kg & 2.42kg and 3.72kg & 3.19kg at the age of 4weeks, 10weeks, 20 weeks 40weeks and 72weeks respectively. Desi male and female attained an average weight of 0.32kg & 0.29kg, 0.96kg & 0.85kg, 1.57kg & 1.48 kg, 2.54kg & 1.88kg and 2.92kg & 2.76kg at the age of 4weeks, 10weeks, 20 weeks 40weeks and 72weeks respectively. Vanaraja shows significantly higher growth rate than RIR and Desi in hill agro-climatic condition. RIR shows early sexual maturity, higher weekly egg lay, higher laying period, higher total egg production and higher eight egg weight than Vanaraja and Desi. The study also shows significant difference in sexual maturity and weekly hen lay between two improved breed in hill agro-climatic condition. The study further shows that the overall mortality and morbidity of Desi was lower than Vanaraja and RIR. The seasonal effect on mortality shows that all the varieties of poultry birds have high mortality rate during rainy season followed by winter months. The study also shows that high return on investment was the major reason for adopting improved poultry breed followed by low investment and high growth rate.